1992
DOI: 10.1159/000200951
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dysfunction amongst Women with Crohn’s Disease: A Hidden Problem

Abstract: The sexual problems of 50 women with Crohn’s disease, of whom 45 had a stable relationship, were investigated by structured interview and compared with age-matched controls. Twenty-four percent patients had either infrequent or no intercourse compared with 4% of controls (χ2 = 8.3, p < 0.005). However, amongst patients and controls who were sexually active, the frequency of intercourse was similar. Reasons for sexual inactivity included abdominal pain (24%), diarrhoea (20%) and fear of faecal incont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
54
0
1

Year Published

1993
1993
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 10 publications
1
54
0
1
Order By: Relevance
“…Some studies have reported an increase in sexual difficulties including dyspareunia in women who have had surgery for IBD and there is some evidence that patients with IBD may delay or even defer pregnancy because of their disease [4,5] . Most of the reports of sexual dysfunction are in women with Crohn's disease.…”
Section: Sexual Healthmentioning
confidence: 99%
“…Some studies have reported an increase in sexual difficulties including dyspareunia in women who have had surgery for IBD and there is some evidence that patients with IBD may delay or even defer pregnancy because of their disease [4,5] . Most of the reports of sexual dysfunction are in women with Crohn's disease.…”
Section: Sexual Healthmentioning
confidence: 99%
“…There is also evidence of substantial sexual dysfunction amongst women with Crohn's disease (CD) [4], In this case-control study we investigated whether such problems were also seen amongst men and women with ulcerative colitis (UC) and men with CD in Leicester.…”
mentioning
confidence: 99%
“…Each patient was posted an invitation to take part in a questionnaire study of possible personal and sexual problems arising from their IBD. 188 o f the 300 patients (6.3%) agreed to participate, and they were subsequently sent a modified version of a previously validated questionnaire on sexual problems [4], Details sought included demographic data, patients' perception of the severity of their illness, data relating to treatment, family histo ry and fertility. The last section dealt with frequency of sexual inter course and any difficulties experienced as well as adverse effects on relationships with partners.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Impacto negativo na vida sexual ocorreu em 27% na faixa etária entre 18 e 54 anos e em 13% naqueles com idades superiores à 55 anos 32 . Nas espondiloartropatias relacionadas à doença inflamatória intestinal (DII), estudos sobre DS mostraram que dispareunia é freqüente 33 e que a depressão é o principal fator determinante de DS 34 .…”
Section: Espondiloartropatiasunclassified